The Influence of Work Engagement on Employee Performance at PT Java Connection Yogyakarta - Ilham, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze and test work engagement on the performance of PT Java Connection employees. This research method uses a quantitative method, with a sample size of 57 where sampling uses a saturated sampling technique, while the data analysis method uses descriptive methods and SEM-PLS. The results of this research show that there is a positive and significant influence between work engagement and employee performance at PT Java Connection. This can be seen from the comparison of t-statistic values ​​and t-table values ​​(3.652 > 1.96) as well as significant p values ​​smaller than 0.05 (0.000 < 0.05), the magnitude of the influence between work involvement and performance is 10.9%, where the remaining 89.1% is influenced by other factors outside this research.